Decreasing the proportion of conflict does not help to exploit congruency cues in a Stroop task - Jiménez, Luis; Gallego, David; Lorda, María José; Méndez, Cástor (Frontiers in Cognition, 2024)
IntroductionHumans are able to regulate the intensity with which they exert cognitive control in interference tasks in terms of factors such as the control level required on the previous trial, and the overall frequency of conflict. However, recent research has shown that the ability to follow explicit cues predicting the required level of control is more limited than previously assumed. Specifically, participants in color Stroop tasks did only take advantage of pre-cues informing them about the congruency of the following trial when the cue was presented in the interval between successive trials, but not when the information was conveyed by the preceding trial.MethodHere we explore the boundary conditions of these sequential cueing effects by using a Stroop task in which the proportion of high-conflict trials was increased, to improve practice with the rules, or decreased, to make the task less demanding.ResultsThe results showed no effect of trial-by-trial cueing, neither increasing nor decreasing the proportion of high-conflict trials. Furthermore, the cueing effect was not observed either when the cue was conveyed by neutral trials, thus reducing the conflation between the conflict present on a trial and the conflict that this trial predicts.DiscussionAs a whole, the results illustrate how difficult it is to adjust control parameters on the fly on the basis of sequential cues, even if they are explicit.